AN ANALYSIS OF CONSUMER BEHAVIOR IN MOBILE PHONE MARKET IN SINDH - Hassan Jawad Soomro; Ikhtiar Ali Ghumro (European Scientific Journal, ESJ, 2013)
This study besides studying brand selection by the young consumers of Sindh will also help to understand the overall purchase behavior of this segment of consumers. The results of this study will provide insight and information for administrators, practitioners, and researchers about the behavior of consumers towards various mobile brands and services particularly in Sindh. The population of the study is students of various universities in Sindh. Descriptive statistics is applied to analyze the characteristics of the respondents. For the testing of hypotheses, exploratory factor analysis with varimax rotation is applied. The results of the current study supports majority of the hypotheses. The results concluded that a large number of respondents prefer the purchase the mobile phone handset with value added facilities like camera, large screen, familiar brand and low price. The respondents also focused those service provider companies that offer the services such as SIM at low rate, free minutes, low call rates and call clarity